Analisis Yuridis terhadap Kasus Pencemaran Nama Baik melalui Media Sosial: Studi Kasus Tuduhan 'Mafia BBM' terhadap AM - Fisensius Samara; Yoseph Gerard Dangga; Alifiyah Khairani Habshari; Andreas Juliano Pedi Radja; Joseano Tedy Petrov Palla; Claudius Siku; Jhon Wesley Malaikosa (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2026)
This research analyzes the legal implications and proof of defamation crimes committed through social media platforms, especially TikTok, within the context of Article 310 paragraph (1) of the Indonesian Criminal Code (KUHP). The case studied involves the alleged defamation against Algajali Munandar, who was publicly accused of being a "Fuel Oil (BBM) Mafia" through a widely distributed video upload. The objective of this research is to examine how the criminal elements, namely attacking one's honor and clear intent for it to be publicly known, can be judicially proven using digital evidence. The analysis results indicate that the serious accusation spread virally on social media clearly fulfills the required elements of the defamation offense. However, this research also highlights a significant trend in law enforcement: the resolution of the case through Restorative Justice. Although the criminal basis was established, the RJ approach was chosen as an alternative to restore the victim's reputation and prevent conflict escalation, thereby demonstrating a shift in the law enforcement paradigm from retributive to reconciliatory. This study concludes that Article 310 of the KUHP remains relevant and effective in prosecuting perpetrators in the digital space, but the RJ mechanism provides a solution that is more oriented toward victim recovery.